Assessing the impact of aflatoxin consumption on animal health and productivity - Atherstone, Christine; Grace, Delia; Lindahl, Johanna F.; Kang'ethe, Erastus K.; Nelson, F. (African Journal of Food, Agriculture, Nutrition and Development, 2016)
Malnutrition is a major problem in East Africa and animal source foods could provide essential protein and micronutrients to help alleviate this. The livestock sector is rapidly growing and intensifying in response to increased consumer demand for animal source foods. However, the ability of the livestock sector to contribute to improving nutritional security is constrained by a number of factors, including contaminants in animal source foods and feeds. Globally, mycotoxins (especially aflatoxins) are the most important contaminants of livestock feed. Aflatoxins are produced by the fungus Aspergillus flavus and related species, which occur naturally in soils throughout sub-Saharan Africa. They are toxic to humans, fish and many other animals, even in low concentrations. Susceptibility to aflatoxins varies by age, health status, species and other factors. Most research has focused on aflatoxins in maize or groundnuts and their impacts on human health. However, aflatoxins are found in other foods and can also impair livestock productivity, reducing the availability of nutritious foods and the income of smallholder farmers. Aflatoxins are also transferred into animal source foods, which could harm consumers. The objective of this review was to synthesize information on the impact of aflatoxins on livestock health and productivity, with a special focus on reports from East Africa. A systematic literature review identified 2700 abstracts in 23 databases. Of these, 46 articles were relevant to the review objective and available. This review summarises key data on impacts of aflatoxins in animal health and levels of aflatoxins in animal source foods. The studies and surveys suggest that aflatoxins may be a significant risk to livestock productivity and food safety in East Africa. Impacts are likely to worsen as livestock industries intensify in response to the growing demand for animal source foods. Climate change may also aggravate aflatoxin problems. In light of this challenge, this review identifies major research gaps and discuss the way forward.